PEMASYARAKATAN HASIL-HASIL PENELITIAN BALAI ARKEOLOGI JAYAPURA - Suroto, Hari (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2011)
Correctional results of archaeological research has been done by the Institute for Archaeology Jayapura consists of exhibitions, seminars, publications in print media, publications in electronic media, publishing, film documentary, archaeological workshops, and websites. Corrections is expected to benefit the academic, practical, and ideological. Correctional activities do not reach out to more stake holders, it is because of the vast territory of Papua and geographical conditions that are difficult to reach, correctional activities for this new archaeological limited in the district / town the Jayapura and District Keerom. Another constraint is human resources and limited funds.